(untitled) (Cambridge, UK, 2002)
Human Population Dynamics introduces theoretical frameworks and methodologies from different traditional disciplines to demonstrate how changes in human population structure can be addressed from several different academic perspectives. The book contains contributions from world-renowned researchers in demography, social and biological anthropology, genetics, biology, sociology, ecology, history and human geography. In particular, the contributors emphasize the lability of many population structures and boundaries, as viewed from their area of expertise.
Keywords: Population,Sociobiology,Social evolution,Demography,Dân số,Sinh học xã hội,Sự tiến hóa xã hội,Dân số học; Congresses,Congresses,Congresses,Congresses,Hội thảo,Hội thảo,Hội thảo,Hội thảo